Upaya Meningkatkan Empati Dalam Berinteraksi Sosial Melalui Dinamika Kelompok Pendekatan Experiential Learning - Wulandari, Septi; Setyowani, Ninik; Mugiarso, Heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
This study was conducted based on the phenomenon that is in junior high school of state 9 Semarang which shows that the students who have empathy in social interactions is low. The purpose of this study to determine the efforts and success in increasing empathy in the social interaction of students through experiential learning approach to group dynamics. This research is action research guidance and counseling. Subjects were 10 students who had low empathy in social interaction. Data collection methods used were psychological scales and observation. Wilcoxon test results obtained thitung 55.0 > 8.0 TTable or imply Ha accepted and Ho rejected. These results demonstrate empathy in students social interaction can be improved after getting the group dynamic experiential learning approach. Empathy in the social interaction of students before gaining experiential learning group dynamics approach to the low category 51.19%. After obtaining the dynamics of group experiential learning approach with 81.96% higher category. After the I cyclus increased empathy in social interactions by 14.93% from the initial conditions. After the II cyclus of empathy in social interactions increased by 15.84% of cyclus I. In addition, students progressing better behavior seen from the increasing indicators sensitive to others, trust, understanding, awareness of others, openness, social contacts, and social communication.